Wildcrafted fermentation : exploring, transforming, and preserving the wild flavors of your local terroir - Baudar, Pascal, 1961- (Chelsea Green Publishing, 2020)
"Fermentation has been used for thousands of years by people all around the world. It is the easiest and safest way to preserve fresh food, and nature provides all that's required: salt, plants, sometimes water, and the beneficial lactic acid bacteria found everywhere. When we ferment a food we transform it, making it more delicious and nutritious and creating new and wonderful flavors that bring it to a whole new level. Today fermented foods have become a hot topic among chefs at high-end restaurants and health-conscious consumers alike. The creative possibilities are endless, especially when we gather and use plants from our local environment. Every landscape, every ecosystem is unique, yet many common edible plants are widely distributed throughout North America and in other regions of the world. In fact, some non-native plants have become so successful that they are considered invasives, or even 'noxious weeds.' Wouldn't it be better to harvest the seasonal bounty and ferment these plants rather than trying to control them with herbicides? In Wildcrafted Fermentation, Pascal Baudar provides all the basic information one needs to make creative ferments at home. From simple wild sauerkrauts and kimchis, to hot sauces, savory pastes, plant-based cheeses, dehydrated spice blends, and much more, Baudar includes over 100 easy recipes that will inspire even the most jaded palate. Wild-gathering greens, stems, roots, berries, fruits, and seeds, each in their season, is a great way to work with your local environment and reconnect with nature in a deeply rewarding and positive way. The recipes are adaptable for people who purchase seasonal and local produce, or harvest from the garden. Knowing the basic methods of fermentation, as well as specific techniques like how to cut and prepare different kinds of plants, provides the confidence to succeed like a pro, the first time and every time. And step-by-step photos of processes and finished dishes will inspire the adventurous home cook to experiment with both wild and cultivated plants. As the author writes, 'Fermentation is an incredible tool if your quest is to create a cuisine unique to you and your environment'"--